The RMSM-X+P: A Minimal Poverty Module for the RMSM-X - Chen, Derek H.C. (World Bank, Washington, D.C., 2013)
The authors present a new tool, the RMSM-X+P, which essentially consists of a RMSM-X model with an additional module for poverty and social indicators. This linkage facilitates the analysis of the impact of various macroeconomic shocks on a selected set of key social indicators. Poverty analysis is performed by the use of a poverty equation (which is estimated using pooled data for a group of low-income countries) that links the incidence of poverty to inflation, the literacy rate, real GDP per capita, the degree of trade openness, and income inequality. Similarly, the authors analyze the effects of various macroeconomic shocks on education and health with the aid of equations for education and health. This new tool allows the user to address a limited number of policy issues. However, it does possess several merits, perhaps the most substantial being that it permits the users to move beyond approaches that focus on the partial correlation between growth and poverty in discussions of poverty reduction.